Feasibility and evaluation of Talk Boost KS2: A school-based programme for oral language skills in children with low-average communication skills in Key Stage 2. (October 2019) - Reeves, Louisa; Freed, Jenny; Wright, Jonathan; Wood, Elizabeth; Black, Rachael; Hartshorne, Mary; Adams, Catherine
Oral language skills in childhood are known to predict literacy levels and academic performance. Identification of children's low-average oral language skills in school is challenging when clear criteria for developmental language disorder are not met. There are few studies of targeted, school-based oral language interventions for the older child. This study aimed to investigate the feasibility of implementing and evaluating a manualized language intervention (Talk Boost KS2) for children aged between 7 and 9 years who were identified as having low-average oral language skills, as delivered by trained teaching assistants in mainstream schools. Twenty-one UK mainstream primary schools each selected eight Year 3 (7–8-year-olds) and Year 4 (8–9-year-olds) children with low-average oral language skills. School staff received training in a new manualized intervention, Talk Boost KS2. Schools were allocated to an Active Intervention (AI) or a Waiting Control condition (WC) condition. The final sample consisted of 162 children of which 87 were allocated to the AI condition and 75 to the WC condition. Progress in favour of the intervention was found on teacher ratings of speech, language and communication needs and on a Learning Behaviours Checklist but not on standardized language or reading comprehension tests. Parents of AI children reported improvements in communication and language skills. Teaching staff reported significant increases in confidence and knowledge in managing children with low-average oral language skills as a result of being involved in the intervention. The findings are discussed in relation to the imperative to provide practical language intervention tools as well as training and support for education staff in order to support children with low-average oral language skills in mainstream schools.